Consumption Discount Rates, Risk Aversion and Wealth in Low-Income Countries: Evidence from a Field Experiment in Rural Ethiopia. (12th June 2018) - Yesuf, Mahmud; Bluffstone, Randall
Abstract: It has been argued that people in low-income countries often have high consumption discount rates (CDRs), which contributes to under-investment in capital, such as education and soil conservation. We use a field experiment to estimate CDRs in rural Ethiopia and find that annual rates range from 43% to 106%. We evaluate whether household wealth affects CDRs and test for synergies with field experiment-derived estimates of risk aversion. We find evidence that respondents who are part of wealthier households have lower CDRs and more risk averse respondents have higher rates.